2016
DOI: 10.1097/yct.0000000000000312
|View full text |Cite
|
Sign up to set email alerts
|

Representations of ECT in English-Language Film and Television in the New Millennium

Abstract: Media depictions of ECT do not reflect current practice. Too often, ECT is portrayed as a torture technique rather than an evidenced-based therapy, and even in a therapeutic setting, it is too often shown with outdated techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 7 publications
1
25
0
1
Order By: Relevance
“…Matthews et al 43 assessed scenes regarding electroconvulsive therapy (ECT) in English-language movies and Low television shows and found that the media still portray ECT in ways that do reflect current practice. Moreover, Bowen et al 44 observed that in the period 2001-2012, articles dealing with personality disorders emphasised the relationship between personality disorder and violent behaviours, encouraging negative stereotypes.…”
Section: Media-monitoring Projects/reporting Guidelinesmentioning
confidence: 99%
“…Matthews et al 43 assessed scenes regarding electroconvulsive therapy (ECT) in English-language movies and Low television shows and found that the media still portray ECT in ways that do reflect current practice. Moreover, Bowen et al 44 observed that in the period 2001-2012, articles dealing with personality disorders emphasised the relationship between personality disorder and violent behaviours, encouraging negative stereotypes.…”
Section: Media-monitoring Projects/reporting Guidelinesmentioning
confidence: 99%
“…Perhaps unsurprisingly, this description itself might sound alien, scientistic, and frightening. Added to this are multiple cultural and media representations situating ECT firmly within the ‘dark side’ of psychiatry ( 6 , 7 ). Most well-known is the iconic 1975 film, One Flew Over the Cuckoo’s Nest , portraying psychiatry as a misused tool of repressive social control.…”
Section: Introductionmentioning
confidence: 99%
“…Added to this are multiple cultural and media representations situating ECT firmly within the ‘dark side’ of psychiatry. 6,7 Most well-known is the iconic 1975 film, One Flew Over the Cuckoo's Nest , portraying psychiatry as a misused tool of repressive social control. Jack Nicholson's character, who is not mentally unwell, forcibly receives ECT, without anaesthetic, as punishment for insubordinate behaviour.…”
mentioning
confidence: 99%
“…More than 80 years after its introduction, electroconvulsive therapy (ECT) remains the most effective treatment for both unipolar and bipolar depression, with response rates of approximately 75% and remission rates of greater than 50% [1]. While the general depiction of ECT in movies and television continues to be of painful and traumatic treatments [2], the FDA recognized the overall safety of ECT devices by reclassifying them as Class II in December 2018. Mandated among the labeling requirements was warnings about the potential for physical trauma including fractures.…”
Section: Introductionmentioning
confidence: 99%